Compartilhamento de banda em redes definidas por software - Carvalho, Glauco Luiz Rezende de (2017)
The paradigm of Software Defined Networks (SDN) has imposed significant changes in the way to manage and operate computer networks through its main idea, the separation of data and control plans. The OpenFlow protocol supports and implements this concept and, due to the many advantages of lower cost of operation and greater ease of adaptation to existing computational projects, is easily found in several commercially available network equipment. With the adoption of the OpenFlow protocol and the SDN paradigm, network innovation and evolution are relatively more favored when compared to the traditional model. In this way, common network services can be evolved, making them increasingly flexible. This dissertation proposes a technique that uses a network based on the SDN architecture and the OpenFlow protocol for the creation of a service for bandwidth sharing, Using the Floodlight controller. Emulations in Mininet virtual environment of experimentation were developed to validate the implemented implementations. For the performance analysis, we studied metrics such as bandwidth, number of packets sent, received and discarded. The results demonstrated the possibility of efficiently achieving bandwidth sharing in SDN networks.